Comparison of image quality between flexible coil and special purpose coil sagittal section on mri manus digit 2-3 - Verina, Alya; Utami, Hernastiti Sedya; Susanto, Fani; Hidayat, Fathur Rachmat; Syafi’ie, Mochammad; Samudra, Alan (Science Midwifery, 2025)
MRI examination of the manus has a challenge in obtaining optimal image quality. Good image quality depends on four characteristics, one of which is the Signal to Noise Ratio (SNR). SNR can be affected by the use of appropriate radiofrequency (RF) coils so that it can increase the SNR value. This study aims to analyze the impact of using different coils on SNR and CNR values, especially in sagittal sections of Proton Density Fat Sat scans. This study is a quantitative study using 10 volunteer samples in the period of February 2025. The results of the study show that the SNR value in the overall anatomy has a p-value <0.05 which means there is a significant difference using flexible coils and special purpose coils. While the SNR value in per-anatomy manus digits 2-3 has a significant difference except for the volar plate anatomy with a p-value = 0.121 meaning there is no significant difference. And compared to flexible coil, the use of special purpose coil in this study has a higher CNR value, especially in the anatomy of the Distal Interphalangeal Joint - Middle Phalanges with an average value of 1221.200. This study provides evidence that the selection of the right coil greatly affects the quality of the resulting image, and the use of special purpose coil is considered to produce better image quality. Therefore, the author recommends the use of special purpose coils in MRI examinations of the manus digits 2-3.